Epithelioid Leiomyosarcoma of Greater Omentum- Case Report of a Rare Tumour - Devendra D. Jalde, A.S. Godhi, Rakesh kumar Pandey*, Satyajit A Godhi, (Recent Research in Science and Technology, 2011)
A 50 year old man presented with a large, circumscribed mass in the abdomen. With ultrasonography, computed tomography, endoscopy and FNAC, preoperative diagnosis could not be made. Complete resection of the mass was performed; the tumor weighed 10.5 kg. Immuno-histochemical study confirmed the diagnosis of epithelioid leiomyosarcoma (ELMS). These are generally solid tumours commonly arising from the stomach. It is uncommon in the greater omentum.